2013
DOI: 10.1007/s12011-013-9790-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Yeast Chromium and l-Carnitine on Lipid Metabolism of Sheep

Abstract: A 56-day feeding experiment was conducted to investigate the effects of yeast chromium (Cr, 300 μg/kg diet) and/or L-carnitine (100 mg/kg diet) on lipid metabolism and their interaction in sheep. After a 14-day adaptation period, 32 3-month-old sheep were randomly divided into four groups of eight. All sheep were fed with basal diets according to the American feeding standard of the National Research Council. At the end of the experiment, yeast Cr and/or L-carnitine supplementation significantly decreased abdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 27 publications
1
8
0
1
Order By: Relevance
“…Urea nitrogen is one of the final products of the protein metabolism in vivo, which can be used to determine the storage of nitrogen. The group supplementation with CY reduced the level of serum UN, TG and TCHO, which was confirmed in the experiment of Zhou (Zhou, Wang, Luo, Niu, & Wang, ). Similarly, Rakhmawati et al () found that TG levels in serum of red tilapia decreased after the addition of CY to feed.…”
Section: Discussionsupporting
confidence: 60%
“…Urea nitrogen is one of the final products of the protein metabolism in vivo, which can be used to determine the storage of nitrogen. The group supplementation with CY reduced the level of serum UN, TG and TCHO, which was confirmed in the experiment of Zhou (Zhou, Wang, Luo, Niu, & Wang, ). Similarly, Rakhmawati et al () found that TG levels in serum of red tilapia decreased after the addition of CY to feed.…”
Section: Discussionsupporting
confidence: 60%
“… Item Diet Dose of yeast Response Source Santa Ines lambs F:C was 40:60 4.87%, 9.73%, and 14.60% inactive dry yeast of diets The subcutaneous fat thickness decreased; meat crude protein and ash increased Rufino et al. (2013) Lambs F:C was 60:40 300 μg yeast-Cr/kg of diet Decreased serum total cholesterol and serum triglyceride levels Zhou et al. (2013) Awassi lambs and Shami goat kids High concentrate diet 12.6 g yeast/kg of diet No effects on growth performance of both lambs and goat kids; increased fat content in the carcass Titi et al.…”
Section: Growth Performance and Quality Of Ruminant Products Following Yeast Treatmentmentioning
confidence: 99%
“…Other reported effects of yeast that could be linked to meat quality include the reduction of serum cholesterol and carcass fat deposition. In lambs, chromium-yeast supplementation has been effective in decreasing the level of blood cholesterol and carcass fat deposition ( Zhou et al., 2013 ), and inactive dry yeast was found to reduce the subcutaneous fat thickness and increase the crude protein percentage of the meat ( Rufino et al., 2013 ). Furthermore, the addition of yeast to the diets of bulls did not affect the level of intramuscular fat or cholesterol composition; however, there was a significant reduction in backfat thickness and an increase in the concentration of free fatty acids in the blood ( Geng et al., 2016 ).…”
Section: Growth Performance and Quality Of Ruminant Products Following Yeast Treatmentmentioning
confidence: 99%
“…Also, fat deposition tends to increase with increasing temperature in sheep ( Degen and Young, 2002 ) which may be related to decreased lipid mobilization as a result of hyperinsulinemia as reported in HS cattle ( O'Brien et al., 2010 ). Dietary Cr can decrease plasma insulin concentrations ( Zhou et al., 2013 ) so may reduce the effects of HS on hyperinsulinemia during maintaining normal insulin action. However, there are no studies investigating the effect of dietary nCrPic on the ability of sheep to counter HS.…”
Section: Introductionmentioning
confidence: 99%